Mathematics
MrsBrown
13

Solve by completing the square , x^2+3x-9=0

+1
(1) Answers
nikolak

x² + 3x - 9 = 0 x² + 3x + (-9) = 0 x = -1 +/- √3² - 4(1)(-9)                 2(1) x = -1 +/- √9 + 36                  2 x = -1 +/- √45              2 x = -1 +/- √(9 × 5)                  2 x = -1 +/- √9 √5                2 x = -1 +/- 3√5              2 x = -1 +/- 3(2.236067978)                       2 x = -1 +/- 6.70820393                     2 x = -1 + 6.70820393    x = -1 - 6.70820393                    2                                  2 x = 5.70820393            x = -7.70820393                2                                   2 x = 2.854101965          x = -3.854101965

Add answer